Standardized production of Phyllanthus tenellus Roxb. by plant tissue culture - Victório, Cristiane; Henriques, Anaize; Tavares, Eliana; Esquibel, Maria Apparecida; Lage, Celso (Revista Ciência Agronômica, 2010)
Exigencies as ethic plant raw material are part of the needs of modern phytotherapy. Micropropagation offers opportunities to obtain mass propagation of superior genotypes in short time. This study aimed to develop a protocol of direct and indirect organogenesis of Phyllanthus tenellus Roxb. Nodal segments from plantlets obtained by in vitro germination were subcultured in modified Murashige and Skoog medium added with different plant growth regulators: IAA (indole-3-acetic acid), IBA (indole-3-butyric acid), GA3 (3-giberelic acid) and KIN (kinetin). The highest proliferation rate was obtained using the combinations: IBA, KIN + GA3 (3.5 mg L-1) and IBA + KIN (2.4 mg L-1). Rooting was intensified after 40 days, reaching 100% for all media with indole-3-butyric acid. Addition of 2,4 dichlorophenoxyacetic acid (2,4D) provided the best results for production of friable calli. Acclimatization was 100% effective for plantlets cultured in control medium, with decrease in survival rate in grown plantlets from media added with growth regulators.